A CMR first strategy in patients with suspected NSTEMI may help identify MINOCA and infarct related artery. (8th February 2021) - Shanmuganathan, M; Barlotti, A; Scarsini, R; Nikolaidou, C; Gara, E; Burrage, M; Terentes-Printzios, D; Kotronias, R; Oxami Study Investigators, 1; Lucking, A; Choudhury, RP; De Maria, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): NIHR Oxford Biomedical Research Centre, British Heart Foundation (BHF), BHF Centre of Research Excellence, Oxford onbehalf: OxAMI study Hypothesis: Up to 14% of patients presenting with suspected non-ST elevation myocardial infarction (NSTEMI) are diagnosed as myocardial infarction with non-obstructive coronary arteries (MINOCA) at invasive coronary angiography (ICA). Additionally, often due to multi-vessel disease (MVD), there is uncertainty regarding the infarct related artery (IRA). We hypothesise that cardiovascular magnetic resonance (CMR) before ICA in NSTEMI patients may: (1) diagnose non-ischaemic aetiologies and therefore reduce the need for ICA; (2) confirm the diagnosis of an acute MI; (3) identify the IRA. Method:  CMR (3T) was performed in NSTEMI patients before ICA in a single tertiary hospital, including cine, T2-weighted (T2w), early and late gadolinium enhancement (LGE) imaging. Interventionalists were blinded to the CMR findings. Two CMR operators blinded to the ICA findings interpreted the CMR scans, including visual assessment of T2w and LGE. Result: 83 patients (69% male, mean age 62 ± 11 years, median (IQR) troponin 1060 (270-3526) ng/L) underwent CMR 38 ± 24 hours post-admission and 9 ± 13 hours pre-ICA. ICA diagnosed 73% MI (52% had MVD) and 27% MINOCA. A CMR-first approach showed 70% acute MI, 16% non-ischaemic pathologies (6% myocarditis, 6% Takotsubo, 4% cardiomyopathy) and 14% no apparent abnormalities.  In MINOCA (n = 22), CMR showed 45% non-ischaemic pathologies (18% Takotsubo, 18% myocarditis, 9% cardiomyopathy), 14% MI and no apparent abnormalities in the rest. In patients with MVD, CMR identified a different acute territory to the IRA identified on ICA in 5%. In the 4% diagnosed with MI on ICA, CMR suggested alternative+/-additional diagnoses. Discussion:  When a CMR diagnosis of non-ischaemic aetiology is considered gold-standard, an ICA diagnosis of MINOCA is limited by 11% inaccuracy (false negative rate 24%; false positive rate 5%).  A CMR-first strategy would have changed management in at least 25% of patients by diagnosing non-ischaemic pathologies and obviating ICA (16%), correctly identifying IRA in MVD (5%) and offering additional diagnoses (4%). Conclusion:   In patients with suspected NSTEMI, a CMR-first strategy is useful in at least 86% of patients by: (1) accurately detecting non-ischaemic aetiologies and avoiding ICA (16%); (2) confirming MI and identifying the acute territory (70%) to guide revascularisation. A CMR-first strategy can change clinical management in at least 25% of NSTEMI patients.